An irregular hexagonal nanosheet-shaped lithium iron oxalate / sodium ion battery negative electrode material
By optimizing the solvent thermal method, irregular hexagonal nanosheet-shaped ferrous oxalate material was solved, and the problem of poor structural stability of ferrous oxalate anode material in lithium/sodium ion batteries was significantly improved.
Patent Information
- Application Number
- CN202211228856.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-10-09
AI Technical Summary
Ferrous oxalate anode material has problems with poor electrochemical activity and poor structural stability of reaction products in lithium/sodium ion batteries, resulting in large irreversible capacity and poor circulation stability for the first time.
By optimizing the solvothermal method, the formation of ferrous oxalate complex is inhibited, the nanocrystal nucleation of the material is promoted and the secondary growth of particles is prevented, and irregular hexagonal nanosheet-shaped ferrous oxalate material is prepared.
It significantly improves the overall structural stability of the material and the efficient and rapid transmission of Li+/Na+ ions, and improves the magnification and cycling performance of lithium/sodium ion batteries.
Smart Images

Figure CN115347186B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an irregular hexagonal nano-sheet-shaped lithium iron oxalate / sodium ion battery negative electrode material, belonging to the technical field of lithium / sodium ion batteries. Background Art
[0002] With the promotion of new energy vehicles, the widespread application of renewable clean energy such as solar energy and wind energy, and the rapid development of strategic emerging industries such as the construction of national smart grids, higher requirements are placed on the energy and power density of lithium / sodium ion batteries. Energy materials are the basis of energy development, but also the bottleneck in energy utilization, so the key to solving energy problems is the breakthrough of energy materials. For lithium / sodium ion batteries, the negative electrode material not only affects the electrochemical performance of the battery, but also plays an important role in its price cost. Therefore, finding a low-cost, good energy and power performance, safe and stable negative electrode material is the key and direction of the current development of lithium / sodium ion batteries. Compared with other negative electrode materials, ferrous oxalate negative electrode materials have outstanding advantages: 1. Higher discharge specific capacity up to; 2. Lower discharge voltage (0.8V); 3. Smaller volume effect (<10%), low requirements for battery design; 4. Excellent rate characteristics; 5. Abundant iron resource reserves, lower raw material cost; 6. Carbon dioxide can be converted into oxalic acid, which can not only solve the source of oxalic acid, but also help alleviate the problem of global carbon emissions.
[0003] Although ferrous oxalate negative electrode materials have the advantages of low price, high specific capacity, and good rate performance, they also have two major problems: large first irreversible capacity caused by poor electrochemical activity of reaction products and poor cycle stability caused by material structural defects. At present, in order to address the above defects, the improvement of oxalate performance is mainly focused on the design of the micro-nano structure of active material particles. By optimizing the micro-nano structure and dimensions of the material through preparation methods and process conditions, Li + / Na + The ion diffusion distance is short, the internal migration channels are multiple, and the particle morphology is stable, so as to obtain the material with high reversible capacity, excellent rate and cycle performance. This method can not only realize Li + / Na + The efficient and rapid insertion / extraction of ions can also buffer the volume effect and shear stress generated during the charge and discharge process, avoid particle breakage and pulverization, and ensure the formation of a stable organic layer and SEI film. However, the design of the micro-nano structure of ferrous oxalate particles is still limited to the control of morphology such as rods, rods, olives, and fibers. + / Na + The research on ion diffusion pathway is still focused on stabilizing and expanding diffusion channels, and there is still little research on multi-directional transmission and multi-channel diffusion control. + / Na+ Starting from the construction of ion diffusion channels, irregular hexagonal nanosheet ferrous oxalate was prepared by optimizing the traditional solvent thermal synthesis process, which can significantly improve the overall structural stability of the material and the Li + / Na + Efficient and rapid ion transport, and improved rate and cycle performance of lithium / sodium ion batteries. Summary of the invention
[0004] In view of the shortcomings of the above technology, the present invention adopts the method of Li + / Na + In order to solve the problems of low ion diffusion rate and poor particle structure stability, a preparation technology of irregular hexagonal nanosheet ferrous oxalate material was developed. The present invention adopts a simple solvothermal technology to inhibit the ferrous oxalate complex - Fe(C 2 O 4 ) n -2(n-1) The formation of irregular hexagonal nanosheet ferrous oxalate is achieved by promoting the nucleation of material nanocrystals and preventing the secondary growth of particles under the action of the solvent.
[0005] First, a soluble ferrous salt is added into deionized water, and stirred to dissolve to obtain a saturated or supersaturated ferrous salt solution; deionized water and anhydrous ethanol are prepared into a mixed solution, and solid oxalic acid is added, and stirred to dissolve to obtain a saturated oxalic acid solution; then the saturated oxalic acid solution is added into the saturated or supersaturated ferrous salt solution, and the reaction process parameters are controlled. After the reaction is completed and naturally cooled, the mixture is filtered and washed, and vacuum dried to obtain an irregular hexagonal nano-sheet ferrous oxalate precursor containing crystal water; finally, under nitrogen or argon inert atmosphere conditions, the obtained precursor is placed in a vacuum tube furnace to control the sintering temperature and sintering time to obtain an irregular hexagonal nano-sheet ferrous oxalate lithium / sodium ion battery negative electrode material.
[0006] The present invention discloses an irregular hexagonal nano-sheet-shaped lithium iron oxalate / sodium ion battery negative electrode material, and the specific preparation method is as follows:
[0007] (1) adding a soluble ferrous salt to deionized water, stirring continuously for 15 to 30 minutes at 10 to 100° C., until a saturated or supersaturated iron salt solution is obtained by dissolving the soluble ferrous salt in deionized water at a mass ratio of 1:5 to 3:1, wherein the soluble ferrous salt is one of ferrous sulfate, ferrous chloride, ferrous nitrate, and ferrous acetate, or a mixture of any of the above;
[0008] (2) Deionized water and anhydrous ethanol are prepared into a mixed solution in a volume ratio of 1:1 to 9:1, and oxalic acid solid is added. The mixture is stirred continuously for 15 to 60 minutes at 10 to 100°C until a saturated oxalic acid solution with a mass fraction of 5% to 50% is obtained, wherein the molar ratio of oxalic acid solid to soluble ferrous salt solid is 1:1 to 1:3. The oxalic acid solution is then added to the above-mentioned ferrous salt solution at a rate of 1 to 30 mL / min and a reaction temperature of 10 to 100°C. The mixture is stirred continuously for 2 to 24 hours. After the reaction is completed and cooled naturally, the mixture is filtered and washed, and then dried in a vacuum for 12 to 24 hours to obtain an irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water.
[0009] (3) Under nitrogen or argon inert atmosphere, the irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water obtained in step (2) is placed in a vacuum tube furnace and sintered at 150 to 300° C. for 1 to 6 h to obtain an irregular hexagonal nanosheet ferrous oxalate lithium / sodium ion battery negative electrode material.
[0010] The principle of the present invention is: the present invention prepares an irregular hexagonal nano-sheet lithium iron oxalate / sodium ion battery negative electrode material by optimizing the solvent thermal method. The present invention provides sufficient Fe 2+ ions, and the inhibitory effect of ethanol solvent on the ionization of ferrous oxalate was used to reduce the C 2 O 4 -2 Solubility of Fe 2+ +C 2 O 4 -2 → FeC 2 O 4 The forward direction proceeds rapidly, and the reaction FeC 2 O 4 + (n-1) C 2 O 4 -2 →Fe(C 2 O 4 ) n -2(n-1) The inhibition of ferrous oxalate complex - Fe(C 2 O 4 ) n -2(n-1) The formation of hexagonal nanosheets was induced, which induced the directional nucleation of the material and inhibited the further growth of the particles. In addition, the presence of ethanol solvent also alleviated the secondary agglomeration and growth between particles, achieving uniform dispersion of irregular hexagonal nanosheet particles.
[0011] The beneficial effects of the present invention are:
[0012] The present invention constructs a multi-directional Li + / Na + Ion diffusion channels achieve efficient ion migration and electron conduction. In addition, the uniform morphology and hexagonal structure also increase the structural stress of the volume effect generated by the material during the ion extraction / embedding process, avoiding particle damage caused by volume expansion. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 is an X-ray diffraction (XRD) diagram of the ferrous oxalate material containing crystal water prepared in Examples 1, 2, and 3 of the present invention;
[0014] Figure 2 is the X-ray diffraction (XRD) diagram of the ferrous oxalate material prepared in Examples 1, 2, and 3 of the present invention;
[0015] Figure 3 is a scanning electron microscope (SEM) image of the ferrous oxalate material prepared in Example 3 of the present invention;
[0016] Figure 4 It is a rate performance diagram of the ferrous oxalate negative electrode material prepared in Examples 1, 2, and 3 of the present invention in a lithium ion battery system;
[0017] Figure 5 It is a cycle performance diagram of the ferrous oxalate negative electrode material prepared in Examples 1, 2, and 3 of the present invention in a lithium ion battery system;
[0018] Figure 6 This is a graph of the cycle performance of the ferrous oxalate negative electrode material prepared in Examples 2 and 3 of the present invention in a sodium ion battery system. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to the described contents.
[0020] Example 1: The preparation method of an irregular hexagonal nanosheet lithium iron oxalate / sodium ion battery negative electrode material in this example is as follows:
[0021] (1) Add ferrous chloride to deionized water and stir continuously at 100°C for 15 minutes until the solution is dissolved to obtain a saturated ferrous chloride solution, wherein the mass ratio of soluble ferrous salt to deionized water is 3:1;
[0022] (2) Deionized water and anhydrous ethanol are prepared into a mixed solution in a volume ratio of 9:1, and oxalic acid solid is added to the mixed solution. The mixture is stirred continuously at 100°C for 15 min until a saturated oxalic acid solution with a mass fraction of 50% is obtained, wherein the molar ratio of oxalic acid solid to ferrous chloride solid is 1:1. The oxalic acid solution is then added to the ferrous chloride solution of step (1), and the addition rate is controlled at 30 mL / min. The reaction temperature is 100°C, and stirring is continued for 4 h. After the reaction is completed and cooled naturally, the mixture is filtered and washed, and then dried in vacuum for 12 h to obtain an irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water;
[0023] (3) Under nitrogen inert atmosphere, the irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water obtained in step (2) is placed in a vacuum tube furnace and sintered at 280° C. for 3 h to obtain an irregular hexagonal nanosheet ferrous oxalate lithium / sodium ion battery negative electrode material.
[0024] Weigh 0.3 g of the irregular hexagonal nanosheet ferrous oxalate material prepared in this embodiment, 0.15 g of acetylene black, and 0.05 g of polyvinylidene fluoride (PVDF), put them in a mortar, grind for 30 min, then add 1 mL of N-methyl-2-pyrrolidone solution, and continue grinding for 20 min. The viscous mixture is evenly coated on the copper foil, and then preliminarily dried at 80 ° C for 15 min, and then dried in a vacuum oven at 80 ° C for 12 h, after which the copper foil is rolled and cut into discs with a diameter of 14 mm to obtain a pole piece.
[0025] In a glove box filled with argon (O 2 content <1ppm, water content <1ppm), the electrode, separator, lithium sheet and nickel foam mesh were assembled into a button battery by a conventional method, and the battery electrochemical performance test was carried out on a constant current charge and discharge system at a current density of 1C=1000 mA / g.
[0026] The X-ray diffraction pattern of the irregular hexagonal nanosheet ferrous oxalate containing crystal water and losing crystal water prepared in this example is as follows: Figure 1 and 2 , the rate and cycle performance of materials with lost crystal water in lithium-ion batteries are shown in the figure Figure 4 and 5 As shown. Figure 1 and Figure 2 It can be seen from the above that the material prepared in this embodiment is pure phase ferrous oxalate. Figure 4 and Figure 5 It can be seen that the material prepared in this example shows excellent rate and cycle performance as a negative electrode material for lithium-ion batteries, at 0.2, 0.5, 1, 2, 3, and 5 A g -1The current densities were 900, 850, 820, 800, 790 and 780 mAh g -1 The discharge capacity at 1 A g -1 After 100 charge-discharge cycles at the same current density, the battery still has a capacity of ~820 mAh g -1 The discharge capacity.
[0027] Example 2: The preparation method of an irregular hexagonal nanosheet lithium iron oxalate / sodium ion battery negative electrode material in this example is as follows:
[0028] (1) Add ferrous nitrate to deionized water and stir continuously for 30 min at 10°C until the ferrous nitrate is dissolved to obtain a supersaturated ferrous nitrate solution, wherein the mass ratio of soluble ferrous salt to deionized water is 1:5;
[0029] (2) Deionized water and anhydrous ethanol are prepared into a mixed solution in a volume ratio of 2:1, and oxalic acid solid is added. The mixture is stirred continuously at 10°C for 60 minutes until a saturated oxalic acid solution with a mass fraction of 5% is obtained, wherein the molar ratio of oxalic acid solid to ferrous nitrate solid is 1:3. The oxalic acid solution is then added to the ferrous nitrate solution of step (1), and the addition rate is controlled at 5 mL / min. The reaction temperature is 10°C, and stirring is continued for 24 hours. After the reaction is completed and cooled naturally, the mixture is filtered and washed, and then dried in vacuum for 12 hours to obtain an irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water;
[0030] (3) Under an argon inert atmosphere, the irregular hexagonal nanosheet ferrous oxalate precursor containing crystalline water obtained in step (2) is placed in a vacuum tube furnace and sintered at 300° C. for 1 h to obtain an irregular hexagonal nanosheet ferrous oxalate lithium / sodium ion battery negative electrode material.
[0031] Weigh 0.3 g of the irregular hexagonal nanosheet ferrous oxalate material prepared in this embodiment, 0.15 g of acetylene black, and 0.05 g of polyvinylidene fluoride (PVDF), put them in a mortar, grind for 30 min, then add 1 mL of N-methyl-2-pyrrolidone solution, and continue grinding for 20 min. The viscous mixture is evenly coated on the copper foil, and then preliminarily dried at 80 ° C for 15 min, and then dried in a vacuum oven at 80 ° C for 12 h, after which the copper foil is rolled and cut into discs with a diameter of 14 mm to obtain a pole piece.
[0032] In a glove box filled with argon (O 2 content <1ppm, water content <1ppm), the electrode, separator, lithium sheet / sodium sheet and nickel foam mesh were assembled into button cells by conventional methods, and the battery electrochemical performance was tested on a constant current charge and discharge system at a current density of 1C=1000 mA / g.
[0033] The X-ray diffraction pattern of the irregular hexagonal nanosheet ferrous oxalate containing crystal water and losing crystal water prepared in this example is as follows: Figure 1 and 2 , the rate and cycle performance of materials in lithium / sodium ion batteries are shown in the figure Figure 4 , 5 and 6. From Figure 1 and Figure 2 It can be seen from the above that the material prepared in this embodiment is pure phase ferrous oxalate. Figure 4 and Figure 5 It can be seen that the material prepared in this example shows excellent rate and cycle performance as a negative electrode material for lithium-ion batteries, at 0.2, 0.5, 1, 2, 3, and 5 A g -1 The current densities were 870, 820, 800, 700, 650, and 600 mAh g -1 The discharge capacity at 1 A g -1 After 100 charge-discharge cycles at the same current density, it still has ~800 mAh g -1 The discharge capacity of Figure 6 It can be seen that the material prepared in this example shows excellent cycle performance as a negative electrode material for sodium ion batteries, and still has a capacity of ~160 mAh g after 20 heavy discharge cycles. -1 The discharge capacity.
[0034] Example 3: The preparation method of an irregular hexagonal nanosheet lithium iron oxalate / sodium ion battery negative electrode material in this example is as follows:
[0035] (1) Add ferrous sulfate to deionized water and stir continuously at 60°C for 15 min until the solution is dissolved to obtain a supersaturated ferrous sulfate solution, wherein the mass ratio of ferrous sulfate to deionized water is 1:1;
[0036] (2) Deionized water and anhydrous ethanol were prepared into a mixed solution in a volume ratio of 1:1, and oxalic acid solid was added. The mixture was stirred continuously at 60°C for 30 min until a saturated oxalic acid solution with a mass fraction of 20% was obtained, wherein the molar ratio of oxalic acid solid to ferrous sulfate solid was 1:1. The oxalic acid solution was then added to the ferrous sulfate solution at a rate of 10 mL / min and a reaction temperature of 60°C. The mixture was stirred continuously for 12 h. After the reaction was completed and cooled naturally, the mixture was filtered and washed, and dried in vacuum for 13 h to obtain an irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water.
[0037] (3) Under nitrogen inert atmosphere, the irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water obtained in step (2) is placed in a vacuum tube furnace and sintered at 280° C. for 3 h to obtain an irregular hexagonal nanosheet ferrous oxalate lithium / sodium ion battery negative electrode material.
[0038] Weigh 0.3 g of the irregular hexagonal nanosheet ferrous oxalate material prepared in this embodiment, 0.15 g of acetylene black, and 0.05 g of polyvinylidene fluoride (PVDF), put them in a mortar, grind for 30 min, then add 1 mL of N-methyl-2-pyrrolidone solution, and continue grinding for 20 min. The viscous mixture is evenly coated on the copper foil, and then preliminarily dried at 80 ° C for 15 min, and then dried in a vacuum oven at 80 ° C for 12 h, after which the copper foil is rolled and cut into discs with a diameter of 14 mm to obtain a pole piece.
[0039] In a glove box filled with argon (O 2 content <1ppm, water content <1ppm), the electrode, separator, lithium sheet / sodium sheet and nickel foam mesh were assembled into button cells by conventional methods, and the battery electrochemical performance was tested on a constant current charge and discharge system at a current density of 1C=1000 mA / g.
[0040] The X-ray diffraction pattern of the irregular hexagonal nanosheet ferrous oxalate containing crystal water and losing crystal water prepared in this example is as follows: Figure 1 and 2 , Scanning electron microscope images of materials Figure 3 , the rate and cycle performance of materials in lithium / sodium ion batteries are shown in the figure Figure 4 , 5 and 6. From Figure 1 and Figure 2 It can be seen from the above that the material prepared in this embodiment is pure phase ferrous oxalate. Figure 2 It can be seen that the material particles prepared in this embodiment are irregular hexagonal nanosheets, and the overall distribution is relatively uniform, without primary particle agglomeration and the like. Figure 4 and Figure 5 It can be seen that the material prepared in this example shows excellent rate and cycle performance as a negative electrode material for lithium-ion batteries, at 0.2, 0.5, 1, 2, 3, and 5 A g -1 The current densities were 1170, 1100, 1050, 1000, 950 and 850 mAh g -1 The discharge capacity at 1 A g -1 After 100 charge-discharge cycles at the same current density, the battery still has a capacity of ~1050 mAh g -1 The discharge capacity of Figure 6It can be seen that the material prepared in this example shows excellent cycle performance as a negative electrode material for sodium ion batteries, and there is still ~230 mAhg after 20 heavy discharge cycles. -1 The discharge capacity.
[0041] Example 4: The preparation method of an irregular hexagonal nanosheet lithium iron oxalate / sodium ion battery negative electrode material in this example is as follows:
[0042] (1) adding ferrous sulfate and ferrous acetate in a molar ratio of 1:1 to deionized water, and stirring continuously at 60°C for 20 minutes until a supersaturated mixed iron solution is obtained, wherein the mass ratio of ferrous sulfate and ferrous acetate solids to deionized water is 1:1;
[0043] (2) Deionized water and anhydrous ethanol were prepared into a mixed solution in a volume ratio of 2:1, and oxalic acid solid was added. The mixture was stirred continuously at 60°C for 30 min until a saturated oxalic acid solution with a mass fraction of 20% was obtained, wherein the molar ratio of oxalic acid solid to ferrous sulfate solid was 1:1. The oxalic acid solution was then added to the mixed iron solution at a rate of 1 mL / min and a reaction temperature of 60°C. The mixture was stirred continuously for 2 h. After the reaction was completed and cooled naturally, the mixture was filtered and washed, and dried in vacuum for 24 h to obtain an irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water.
[0044] (3) Under an argon inert atmosphere, the irregular hexagonal nanosheet ferrous oxalate precursor containing crystalline water obtained in step (2) is placed in a vacuum tube furnace and sintered at 150° C. for 6 h to obtain an irregular hexagonal nanosheet ferrous oxalate lithium / sodium ion battery negative electrode material.
[0045] The specific implementation modes of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. An irregular hexagonal nanosheet lithium iron oxalate / sodium ion battery negative electrode material, characterized in that: The specific preparation steps are as follows: (1) adding a soluble ferrous salt to deionized water, stirring continuously for 15 to 30 minutes at 10 to 100° C., until the ferrous salt solution is dissolved, wherein the ferrous salt solution is a saturated or supersaturated solution, wherein the soluble ferrous salt is one of ferrous sulfate, ferrous chloride, ferrous nitrate, and ferrous acetate, or a mixture of any of the above, and the mass ratio of the soluble ferrous salt to deionized water is 1:5 to 3:1; (2) Deionized water and anhydrous ethanol are prepared into a mixed solution in a volume ratio of 1:1 to 9:1, and oxalic acid solid is added to the mixed solution. The mixture is stirred continuously for 15 to 60 minutes at 10 to 100° C. until the oxalic acid solution is dissolved and the oxalic acid solution is a saturated solution with a mass fraction of 5% to 50%. The oxalic acid solution is then added to the iron salt solution obtained in step (1) at a rate of 1 to 30 mL / min and a reaction temperature of 10 to 100° C. The mixture is stirred continuously for 2 to 24 hours. After the reaction is completed and cooled naturally, the mixture is filtered and washed, and then vacuum dried for 12 to 24 hours to obtain an irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water; (3) Under nitrogen or argon inert atmosphere, the irregular hexagonal nanosheet ferrous oxalate precursor containing crystal water obtained in step (2) is placed in a vacuum tube furnace and sintered at 150 to 300° C. for 1 to 6 h to obtain an irregular hexagonal nanosheet ferrous oxalate lithium / sodium ion battery negative electrode material.
2. The irregular hexagonal nanosheet lithium iron oxalate / sodium ion battery negative electrode material according to claim 1, characterized in that: The molar ratio of the oxalic acid solid in step (2) to the soluble ferrous salt solid in step (1) is 1:1 to 1:3.